THE IMPACT OF DOCUMENTARY DIGITAL STORYTELLING ON CRITICAL THINKING AND READING SKILLS IN HIGH SCHOOL STUDENTS - Awaliyah, Lela; Pratiwi, Dwiyani (English Review: Journal of English Education, 2024)
This study aims to evaluate the effect of a digital storytelling-based documentary video method in developing critical thinking skills on reading comprehension of secondary school students, considering learning style as a moderator. The method was applied to the experimental group, while the control group used the conventional method. The pretest results showed that the experimental group had an average score of 84.7, higher than the control group, which had an average score of 81.36. After the treatment, the experimental group showed a significant improvement with an average posttest score of 87.63, compared to the control group, which had an average score of 83.7. ANOVA analysis showed that learning style had a significant effect on critical thinking ability (sig = 0.036), while membership in the treatment or control group showed no significant effect (sig = 0.581). No significant interaction between learning style and group was found (sig = 0.171), indicating that the effect of learning style on critical thinking development was independent of the treatment group. This study confirmed that customizing learning methods according to students' learning styles can improve critical thinking skills in reading comprehension. However, the effectiveness of this method was not significantly affected by membership in the treatment or control group. Further research is needed to explore how this method can be optimized for different groups of students.